Synthesis, X-ray crystal structure, thermal behavior and spectroscopic analysis of 1-(1-naphthoyl)-3-(halo-phenyl)-thioureas complemented with quantum chemical calculations - Saeed, Aamer (2015)
Two novel 1-(1-naphthoyl)-3-(halo-phenyl) substituted thioureas, namely 1-(1-naphthoyl)-3-(2,4-di-fluoro-phenyl)-thiourea (1) and 1-(1-naphthoyl)-3-(3-chloro-4-fluoro-phenyl)-thiourea (2), were synthesized and fully characterized. The X-ray crystal and molecular structures have been determined resulting in a planar acylthiourea group, with the Cdouble bondO and Cdouble bondS adopting a pseudo-antiperiplanar conformation. An intramolecular Nsingle bondH⋯Odouble bondC hydrogen bond occurs between the thioamide and carbonyl groups. The crystal packing of both compounds is characterized by extended intermolecular Nsingle bondH⋯Sdouble bondC and Nsingle bondH⋯Odouble bondC hydrogen-bonding interactions involving the acylthiourea moiety. Compound 2 is further stabilized by π-stacking between adjacent naphthalene and phenyl rings. The thermal behavior, as well as the vibrational properties, studied by infrared and Raman spectroscopy data complemented by quantum chemical calculations at the B3PW91/6-311++G(d,p) support the formation of these intra- and intermolecular hydrogen bonds. Furthermore, the UV–Vis spectrum is interpreted in terms of TD-DFT quantum chemical calculations with the shapes of the simulated absorption spectra in good accordance with the experimental data.